Pengaruh Profitabilitas Pengaruh Profitabilitas, Ukuran Perusahaan, Leverage, Capital Intensity Terhadap Tax Avoidance: Studi Empiris Pada Perusahaan Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2021-2023 - Lufi Rahayu; Lintang Kurniawati (AKUA: Jurnal Akuntansi dan Keuangan, 2025)
The phenomenon of tax avoidance carried out by several companies is a strategy used to minimize tax obligations without violating applicable laws. In the taxation system in Indonesia which uses the Self-Assessment System, corporate taxpayers have an active role in reporting and calculating their taxes. However, in the provisions of the practice of Tax Avoidance, it is often used by several companies to reduce the tax burden in order to increase net profit income. Although legal, this practice can have a very significant impact and also pose a challenge for the government in optimizing tax revenues. Factors such as Profitability, Company Size, Leverage, and Capital Intensity are the main determinants in tax calculations. Companies tend to explore loopholes in tax regulations that are useful for reducing the tax burden, ultimately impacting the realization of state tax revenues. The government is still trying to overcome this problem with various policy handlings that have been implemented, including tax incentives to encourage annual tax compliance. This research study highlights the dynamics that occur between corporate and government interests in tax policy and the impact of Tax Avoidance on the Indonesian economy.